The effects of cigarette smoking on hemoglobin levels compared between smokers and non-smokers - Shah, BK; Nepal, AK; Agrawal, M; Sinha, AK (Sunsari Technical College Journal, 2013)
Background: Smoking is one of the global problems causing different disease. Smoking cause variation in different parameters of blood among which hemoglobin is believed to be increased due to smoking. Objective: To compare the effect of cigarette smoking on hemoglobin levels between smokers and non smokers. Materials and methods: A cross-sectional comparative study was conducted in Department of Pathology, Hematology Laboratory, B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Total of 100 sample size which compromised of 50 smokers and 50 non smokers were included the study. Hemoglobin was estimated by Cyanmethemoglobin method. Student ‘t’ test was applied for parametric data and Chi- Square test was applied for categorical data. A p-value less than 0.05 was considered statistically significant. Results: Mean±SD of hemoglobin for smokers was 14.14±1.3 g/dl and for non smokers was 12.37±2.36 g/dl. The awareness about smoking effect in both smokers and non smokers group was not significantly different (p=0.15). Similarly the mean±SD age was 32.78±9.27 years for smokers and 35.68±11.11 years for non smokers, and was not significantly different (p=0.18). Conclusion: The present study showed that the hemoglobin level of smoker group was higher than the non-smoker group. Further substantial studies in large population should be conducted to generalize this findings. DOI: http://dx.doi.org/10.3126/stcj.v1i1.7985 Sunsari Technical College Journal Vol.1(1) 2012 42-44